Identification of B cell antigens in solid cancer: initial insights and functional implications - Yang, Jung-In; Moresco, Philip; Fearon, Douglas; Yao, Min (Frontiers in Immunology, 2025)
Cancer antigen discovery has mostly focused on T cell antigens, while antigens driving B cell responses have been largely overlooked despite representing another important branch of adaptive immune responses in cancer. Traditional B cell antigens in cancer have been studied using serological approaches analyzing polyclonal antibodies in serum. With recent technological advances in single-cell sequencing, a few studies have begun to investigate single B cell antigen specificity in the tumor microenvironment using immunoglobulin single-cell sequencing, recombinant monoclonal antibody production, cancer binding screening, and antigen identification. In this review, we highlight the initial insights into B cell directed cancer antigens and categorize them into cancer-associated viral antigens and non-viral antigens, with the latter featuring autoantigens. We will further discuss the functions of B cells in cancer in the context of their antigen specificity, and categorize their functions into antibody effector function, T cell activation, and B cell secretion. Lastly, we will provide perspectives on the challenges and opportunities in the identification of new B cell cancer antigens and highlight their translational potential.